Android multi-threading program execution on single and multi-core CPUS with matrix multiplication - B. Sallow, Amira (International Journal of Engineering and Technology, 2019)
Most problems involving complex computations can be solved by implementing them using Chip Multiprocessor (CMP) approach characterized by high speed, high performance for personal computers and mobile devices. In this paper Android multi-threading Program for matrix multiplication executed on single and multi-core CPUs. the use of this technology greatly reduced the time required to execute the code of the matrix multiplication for great size loads. The main goal of this paper is to compare the single-core technique with CMP approach to execute Android matrix multiplication Program on single and multi-core CPUs and see what limitations in single-core architecture triggered the transition to CMPs, and to know that the use of this technology greatly reduced the time required to execute code of matrix multiplication for great size loads. The results show that the parallel algorithm outperformed the sequential algorithm by an average of speedup equal to 5.2. Â